2015
DOI: 10.1007/s13197-015-1746-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different brewing conditions on catechin content and sensory acceptance in Turkish green tea infusions

Abstract: The optimal brewing conditions for Turkish green tea were determined on the basis of extracted catechins and sensory attributes. Green tea infusions were prepared at 75, 85 and 95°C with brewing times of 1, 2, 3, 5, 10, 20, 30 and 45 min. The amounts of epistructured catechins (EGCG, EGC, ECG, EC), non-epistructured catechins (C, GC, GCG) and caffeine in brewed tea samples were analysed. Sensory analyses were performed by nine trained panelists for infusion colour, taste, aroma and overall acceptability. Brewi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
70
2
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(88 citation statements)
references
References 13 publications
12
70
2
4
Order By: Relevance
“…However these nonvolatile constituents were identified as driver of consumer disliking of green tea products. Previous work also reported that the catechins influenced the overall flavor and provided bitter and astringency characteristics of green tea (Lee and Chambers 2011;Saklar et al 2015). The finding from current work also support the previous findings.…”
Section: Consumer Acceptabilitysupporting
confidence: 89%
“…However these nonvolatile constituents were identified as driver of consumer disliking of green tea products. Previous work also reported that the catechins influenced the overall flavor and provided bitter and astringency characteristics of green tea (Lee and Chambers 2011;Saklar et al 2015). The finding from current work also support the previous findings.…”
Section: Consumer Acceptabilitysupporting
confidence: 89%
“…The highest catechins content was obtained form thermal processed at 70°C for 1 minutes (95.480 mg/L), while the lowest one was at 90°C for 5 minutes (28.593 mg/L). And this result is similar to one reported by Saklar et al, (2015) stated that the increase brewed up to temperature 80° C for 3 minutes can decrease in the amount of catechins obtained 50,69 mg/100 ml. Acording to Figueroa et al (2004), the range catechins found in green tea were between 35-45%, in the formepigallocatechingallate.…”
Section: Catechins Test Resultssupporting
confidence: 92%
“…Effect of infusion conditions on bioactive compounds extraction has been studied (Araújo Ramalho et al 2013;Bae et al 2015;Rusak et al 2008) showing that temperature and time are the most crucial parameters affecting polyphenol content and antioxidant capacity (Araújo Ramalho et al 2013;Damiani et al 2014). For best extraction of antioxidant compounds from green tea it is recommended to employ low temperatures (Banerjee and Chatterjee 2014), since over 90°C polyphenols are destroyed and sensory properties have been found to decrease (Saklar et al 2015); agitation and dosage form have no important influence (Samaniego-Sánchez et al 2011).…”
Section: Introductionmentioning
confidence: 99%